2015
DOI: 10.1007/s12011-015-0344-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Supplementation on Apoptosis and Cell Cycle Blockage of Renal Cells in Broilers Fed a Diet Containing Aflatoxin B1

Abstract: The aim of the study was to investigate the competency of selenium (Se) in counteracting the adverse effects of aflatoxin B1 (AFB1) on apoptosis, cell cycle, and proliferation of nephritic cells. Two hundred forty 1-day-old healthy male avian broilers were randomly divided into four groups and fed basal diet (control group), 0.3 mg/kg AFB1 diet (AFB1 group), 0.4 mg/kg Se diet (+Se group), and 0.3 mg/kg AFB1 + 0.4 mg/kg Se diet (AFB1 + Se group), respectively. Compared to the control group, the number of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…The apoptotic cells could be evaluated by Flow cytometry and TUNEL assay [ 38 , 39 ]. Our present research revealed an increased apoptosis in the AFB 1 group demonstrated by TUNEL and flow cytometry, suggesting that AFB 1 could lead excess apoptosis in the chickens’ splenocytes, in line with previous researches in thymocytes [ 19 , 22 ], bursa of Fabricius cells [ 27 ] and renal cells [ 26 ]. Lymphocytes are the main components within the lymphoid organs, and severe lymphocyte depletion in the lymphoid organs was due to apoptosis [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The apoptotic cells could be evaluated by Flow cytometry and TUNEL assay [ 38 , 39 ]. Our present research revealed an increased apoptosis in the AFB 1 group demonstrated by TUNEL and flow cytometry, suggesting that AFB 1 could lead excess apoptosis in the chickens’ splenocytes, in line with previous researches in thymocytes [ 19 , 22 ], bursa of Fabricius cells [ 27 ] and renal cells [ 26 ]. Lymphocytes are the main components within the lymphoid organs, and severe lymphocyte depletion in the lymphoid organs was due to apoptosis [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis has an important role in deveolpment, differentiation, proliferation and homeostasis of cell, tissue and organ [ 35 ]. AFB 1 directly or indirectly activated apoptotic process [ 36 , 37 ], inducing apoptosis of several poultry and mammal cells [ 8 , 9 , 17 , 19 , 21 26 ]. The apoptotic cells could be evaluated by Flow cytometry and TUNEL assay [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scott et al [2] have demonstrated that AFB 1 treatment can lead to an accumulation of chicken thymocytes in G 2 /M phase in vitro . Our previous studies suggest that AFB 1 induced jejunal cell arrest at G 2 /M phase and renal cell arrest at G 0 /G 1 phase in broilers [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, dietary addition of selenium yeast partially counteracted the negative effects of AFB 1 on weight gain and death rate [ 22 ]. Dietary Se could relieve liver lesion [ 23 ] and immunosuppression [ 24 ] induced by AFB 1 , and could protect renal cells from oxidative stress in vitro [ 25 ], and inhibit AFB 1 -induced apoptosis and cell cycle blockage in renal cells of broiler [ 26 ].…”
Section: Introductionmentioning
confidence: 99%